Malliavin calculus for Markov chains using perturbations of time. Issue 6 (17th August 2016) - Denis, Laurent; Nguyen, Tuyet Mai
Abstract : In this article, we develop a Malliavin calculus associated to a time-continuous Markov chain with finite state space. We apply it to get a criterion of density for solutions of stochastic differential equation involving the Markov chain and also to compute greeks.